New indolizines with phenanthroline skeleton: Synthesis, structure, antimycobacterial and anticancer evaluation. Issue 10 (15th May 2015) - Danac, Ramona; Al Matarneh, Cristina M.; Shova, Sergiu; Daniloaia, Teofil; Balan, Mihaela; Mangalagiu, Ionel I.
Graphical abstract: Abstract: We report herein a feasible study concerning the design, synthesis, structure and in vitro antimycobacterial and anticancer activity of two new classes (containing four and five fused rings) of indolizine with phenanthroline skeleton. The preparation is straight and efficient, involving a Huisgen [3+2] dipolar cycloaddition of cycloimmonium ylides to alkynes or alkenes dipolarophiles. The cycloaddition reactions are highly stereo- or regioselective, according with the dipolarophiles nature. The structure of the new compounds was assigned unambiguously, X-ray analysis including. The primary antimycobacterial screening reveals that one of the thirteen tested compounds had a good activity against Mycobacterium tuberculosis H37Rv under aerobic conditions. The antiproliferative evaluation against a NCI 60 human tumor cell line panel, revealed that two indolizine with phenanthroline skeleton exhibit a selective and significant antitumor growth inhibitory activity against Breast Cancer (MCF7 and T-47D) and a slightly moderate activity against some forms of Leukemia, Non-Small Cell Lung Cancer, Renal Cancer and Breast Cancer (MDA-MB-468). The X-ray diffraction study of the indolizines with phenanthroline skeleton prove a flat coplanar structure which, corroborated with their anticancer activity, allow us to suggest that an interaction with DNA (via an intercalation mechanism) would be reasonable.